2013
DOI: 10.1002/elan.201300134
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Sulfide by Hematoxylin Multiwalled Carbon Nanotubes Modified Carbon Paste Electrode

Abstract: This study investigates a new approach for the amperometric determination of sulfide using a hematoxylin multiwalled carbon nanotubes modified carbon paste electrode (HM‐MWCNTs/CPE). The experimental results show that HM‐MWCNTs/CPE significantly enhances the electrocatalytic activity towards sulfide oxidation. Cyclic voltammetric studies show that the peak potential of sulfide shifted from +400 mV at unmodified CPE to +175 mV at HM‐MWCNTs/CPE. The currents obtained from amperometric measurements at optimum con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…According to curve b of Figure 8, the oxidation of sulfide at the 3DIGF/PMTC‐modified ITO electrode began at ∼−0.4 V (vs. Ag/AgCl) and was followed by a peak at a potential of ∼−0.24 V (vs. Ag/AgCl). The 3DIGF/PMTC electrocatalyst has a very high electrooxidation peak current density of ∼500 μA/cm 2 , which is much higher than most of the previously reported electrochemical sulfide oxidation electrocatalysts [38,93–106] . 3DIGF/PMTC could be an excellent candidate for developing a sensitive and selective sulfide sensor in aqueous solutions.…”
Section: Resultsmentioning
confidence: 79%
“…According to curve b of Figure 8, the oxidation of sulfide at the 3DIGF/PMTC‐modified ITO electrode began at ∼−0.4 V (vs. Ag/AgCl) and was followed by a peak at a potential of ∼−0.24 V (vs. Ag/AgCl). The 3DIGF/PMTC electrocatalyst has a very high electrooxidation peak current density of ∼500 μA/cm 2 , which is much higher than most of the previously reported electrochemical sulfide oxidation electrocatalysts [38,93–106] . 3DIGF/PMTC could be an excellent candidate for developing a sensitive and selective sulfide sensor in aqueous solutions.…”
Section: Resultsmentioning
confidence: 79%
“…Fig. 7A depicts the CV response of PLL-modified electrode in various pH solutions (3)(4)(5)(6)(7)(8)(9)(10)(11) containing 2 mM sulfide at 50 mV s −1 . It is worthy to mention that the oxidation peak current of sulfide ion was decreased upon increasing or decreasing the pH = 7.…”
Section: Resultsmentioning
confidence: 99%
“…4,5 However, the high concentration level of sulfide can lead to serious disorders such as personal distress, unconsciousness, irritation of mucous membranes, permanent brain damage or even death. 2,[6][7][8] Therefore, the accurate and low level detection of sulfide is much important for both an environmental and human health. Thus, we have developed a simple and cost effective electrochemical sensor for the determination of sulfide ions in water samples.…”
mentioning
confidence: 99%
“…Long et al. investigated a new approach for the amperometric determination of sulfide that uses a hematoxylin MWCNT‐modified carbon‐paste electrode (CPE@HM‐MWCNTs) [62] . Results indicated that the CPE@HM‐MWCNTs substantially improve the electrocatalytic activity for sulfide oxidation.…”
Section: Sulfide Sensing Strategies In Controlled Potential Techniquesmentioning
confidence: 99%